The Role of Islamic Education in Constructing Family Resilience: A Socio-Theological Study - Baiq Citra Handayani; Muhammad Ahyar; Wardi Sahri; Lalu Agus Murzaki; Abdussyakur Abdussyakur (JURNAL ISLAM NUSANTARA, 2025)
This study aims to examine how Islamic education contributes to the construction of family resilience through socio-theological mechanisms in West Nusa Tenggara (NTB), Indonesia. In the context of rapid modernisation, socio-economic vulnerability, and recurrent natural disasters, families face increasing pressures that threaten stability and adaptive capacity. Previous studies on family resilience have emphasised psychological and structural factors but have insufficiently examined the role of religion and education in highly religious societies. This research employs a qualitative embedded single-case study design focusing on pesantren, majlis taklim, and resilient family units across Lombok and Sumbawa. Data were collected through in-depth interviews, participant observation, and document analysis and were analysed thematically using Family Resilience Theory and Social Capital Theory within a socio-theological framework. The findings reveal three interrelated processes. First, theological meaning-making rooted in tawakkul, sabr, and syukr enables families to reinterpret crises as purposeful divine tests, strengthening emotional regulation and optimism. Second, religious institutions function as social capital networks that provide trust-based support, collective problem-solving, and material assistance. Third, pedagogical transmission of family ethics and roles embeds moral discipline, adaptive communication, and relational responsibility in daily family life. These findings extend family resilience and social capital theories through an Islamic socio-theological lens and highlight Islamic educational institutions as strategic sites for resilience-building. Policymakers and educators are encouraged to integrate family counselling and psychosocial support into Islamic educational curricula.